Description of two new species of the leafhopper genus Karachiota (Hemiptera: Cicadellidae: Typhlocybinae: Dikraneurini ) from China - Jiao, Meng (Zootaxa, 2015)
Two new species of the dikraneurine leafhopper genus Karachiota Ahmed are reported from China: Karachiota recurva sp. nov. and Karachiota aristata sp. nov.. A key of all species of the genus is provided.